PERAN INVESTASI DAN TENAGA KERJA DALAM MENINGKATKAN LAJU PERTUMBUHAN EKONOMI DI PROVINSI NUSA TENGGARA BARAT - Indrani, Sarah Meirizki; Rachman, Rosyidah (Pusat Riset dan Publikasi, 2024)
This study aims to examine the role of investment and labor in increasing the rate of economic growth in West Nusa Tenggara Province in 2012-2021. The type of this study was associative study. The type of data used was quantitative in the form of GDP, investment and labor data for West Nusa Tenggara Province obtained from existing sources in the form of archives or documents that had been compiled and published by the Central Statistics Agency (BPS) of West Nusa Tenggara Province. In this study, researchers use documentation techniques to collect data from secondary sources. Data analysis was carried out using multiple linear regression analysis, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient testing (R2). The results of this study showed that investment and labor had a positive and significant effect on economic growth in West Nusa Tenggara Province, both partially and simultaneously. The ability of investment and labor to effected economic growth in West Nusa Tenggara Province was 67%, while the remaining of 33% was effected by other variables outside this study model, such as human capital, capital expenditure, and labor force participation rate.